2014
DOI: 10.2320/matertrans.m2014245
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Particle Simulation of Gas Bubble Passing Through Liquid/Liquid Interfaces

Abstract: A newly developed computational fluid dynamics (CFD) model based on a multi-phase particle method is presented for predicting the entrainment behavior of liquid metal into slag due to rising single bubble. By comparing results calculated using this model against experimental data, it was found that the transient behavior of bubbles and the two immiscible liquids can be accurately estimated by this method. The rupturing of the thin water film surrounding the bubble was less reliably predicted, but this 3-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…This procedure is similar to that used in our previous study. 23) Using this procedure, we observed that the rising bubble began to modify the SPTS-SO interface by pulling the SPTS phase upward through their interface.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure is similar to that used in our previous study. 23) Using this procedure, we observed that the rising bubble began to modify the SPTS-SO interface by pulling the SPTS phase upward through their interface.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 shows the experimental setup used. The experiments were performed in an air-conditioned room at a fixed temperature of 293 K. First, an acrylic tank (inner dimensions: 0.040 × 0.090 × 0.295 m; with this tank design, the wall effect does not affect bubbles and the thin film is easy to observe [21,22]) was filled with the two liquid phases (height of each phase: 0.090 m). The aqueous SPT solution was the lower liquid phase (liquid 1), while SO (KF-96-10cs, Table I shows the physical properties of each solution [23][24][25].…”
Section: Methodsmentioning
confidence: 99%
“…To calculate the surface tension, we used the inter-particle potential model. [29][30][31][32][33] We modeled the droplets as cubes with side lengths L50:050 m. For the liquid phase, we used water, and to verify the theoretical solution for the vibration period, we assumed conditions of non-viscosity, and a uniform melt. Figure 4 shows the calculated results for droplet vibration in each condition.…”
Section: Verificationmentioning
confidence: 99%
“…We analyzed droplet motion for respective cases in which the particle number was changed. To calculate the surface tension, we used the inter‐particle potential model . We modeled the droplets as cubes with side lengths L=0.050 normalm.…”
Section: Droplet Incompressible Flow Simulationmentioning
confidence: 99%